NANOSTRUCTURED MATERIALS FOR EFFICIENT CATALYSIS IN CHEMICAL REACTIONS - Park Jihoon; Ri Hwa Sin; Erdenetsetseg Chuluunbaatar (Yayasan Adra Karima Hubbi, 2025)
The quest for more efficient catalytic materials has intensified due to the growing demand for sustainable chemical processes. Nanostructured materials have emerged as promising candidates, offering enhanced surface area and reactivity, which can significantly improve catalytic performance. This study aims to investigate the role of nanostructured materials in catalysis, focusing on their synthesis, characterization, and application in various chemical reactions. The goal is to identify the optimal conditions for maximizing catalytic efficiency. A series of nanostructured catalysts were synthesized using sol-gel and hydrothermal methods. Characterization techniques, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD), were employed to analyze the structural and morphological properties of the materials. Catalytic performance was evaluated through various model reactions, such as hydrogenation and oxidation. The findings revealed that nanostructured materials exhibited significantly higher catalytic activity compared to their bulk counterparts. Specific catalysts demonstrated up to a 70% increase in reaction rates, attributed to their enhanced surface area and active sites. The study also identified optimal synthesis parameters that further improved catalytic performance. This research highlights the potential of nanostructured materials to revolutionize catalysis in chemical reactions. By optimizing synthesis methods and understanding the relationship between structure and activity, it is possible to develop more efficient catalysts for sustainable chemical processes.